SiO2-metal oxide composite material with high specific surface area as well as preparation method and application thereof

By adding polyhydroxy polymer compounds to the preparation process of SiO2-metal oxide composite, the problem of aggregation and growth of metal oxides during drying and calcining is solved, and a composite material with a high specific surface area is prepared, which improves material performance and simplifies the process.

CN119701969APending Publication Date: 2025-03-28TAIYUAN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411893213.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing metal oxide-SiO2 composite materials have a growing problem of metal oxide aggregation during drying and calcining, resulting in a decline in material performance, complex process and uneco-friendly.

Method used

By adding polyhydroxy polymer compounds to the mixing process of silicon source, metal salt and solvent, the collapse of SiO2 structure and the aggregation and growth of metal oxides are inhibited, and a SiO2-metal oxide composite material with a high specific surface area is prepared.

Benefits of technology

The preparation of metal oxides in SiO2 structures is realized with nanoparticles, which improves the specific surface area and catalytic activity of the material, and has a simple process, environmental protection and good economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701969A_ABST
    Figure CN119701969A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbents and chemical catalysts, and particularly relates to a SiO2-metal oxide composite material with a high specific surface area as well as a preparation method and application of the SiO2-metal oxide composite material. According to the preparation method, a polyhydroxy high-molecular compound is added in the mixing process of a silicon source, metal salt and a solvent, and the SiO2-metal oxide composite material is prepared. According to the composite material, hydroxyl and hydroxyl of solvent molecules are used for competitively adsorbing a silicon source precursor and metal ions, the solvent molecules are squeezed away, the degree of freedom of the metal ions is limited, and the problems of SiO2 structure collapse and metal oxide aggregation and growth in the solvent removal process of drying, roasting and the like are effectively solved. The composite material is high in specific surface area, the metal oxide is highly dispersed in the SiO2 structure in the form of nanoparticles, and when the composite material is used for adsorbing CO2, the adsorbing capacity of CO2 is large; when the catalyst is used for catalyzing a reverse water gas shift reaction, the catalyst has high activity and high selectivity. The method has the advantages of being simple in technological process, easy to control, environmentally friendly, good in economical efficiency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adsorbents and chemical catalysts, and specifically relates to a high specific surface area SiO 2 -Metal oxide composite materials and their preparation methods and applications. Background Art

[0002] Mesoporous silica (SiO 2 ) has the advantages of high specific surface area, developed three-dimensional pore structure, abundant surface hydroxyl groups (Si-OH), strong mechanical strength and high thermal stability. It is widely used as an adsorption material in the field of environmental protection to adsorb and remove CO in the atmosphere. 2 It can also be used to remove small molecules of volatile organic gases (VOCs), toxic heavy metal ions in wastewater, etc. It is also often used in the field of catalysis as a carrier material for catalysts to improve the dispersion and morphology of metals to achieve the purpose of improving reaction activity and regulating product selectivity.

[0003] In recent years, in order to further improve SiO 2 The adsorption and catalytic properties of the material, the researchers introduced metal oxides into SiO 2 Materials, preparation of SiO 2 -Metal oxide composite materials. The surface of the introduced metal oxides mostly has a certain acidity (such as ZnO, Al 2 O 3 The composite material has a high adsorption capacity and a high catalytic performance. In addition, when the metal oxide is highly dispersed in the SiO 2 In the three-dimensional structure of metal oxide, the metal sites of metal oxide are closely related to SiO 2 The hydroxyl sites of the catalyst are closely adjacent to each other, and the distance between them is often at the nanometer scale, which is conducive to the synergistic effect between them. This synergistic effect includes: (1) in terms of adsorption, the two sites jointly adsorb adsorbate molecules, thereby significantly enhancing the adsorption strength and adsorption amount; (2) in terms of catalysis, the two sites jointly adsorb and activate reactant molecules, or the two sites jointly stabilize the key intermediate species of the reaction, thereby significantly improving the activity of the catalyst; in addition, when the two sites participate in different elementary reaction steps, the product selectivity can be regulated by changing the reaction path.

[0004] Therefore, for SiO 2 - For metal oxide composite materials, in order to improve their performance as adsorption or catalytic materials, it is often necessary to develop preparation methods to make the metal oxides highly dispersed in the form of nanoparticles on SiO 2This can not only fully expose the surface acid / base / hydroxyl sites of the metal oxide itself, but also promote the bonding of the metal oxide with SiO 2 The most commonly used methods currently include: (1) first synthesizing metal oxide nanoparticles or metal-organic polymers, then mixing them with silica sol or gel precursors, and then drying, calcining and other processes to obtain composite materials; (2) metals are mixed with silicon source molecules in ionic form, and a composite wet gel is obtained through a sol-gel process, which is then dried to obtain a composite material. It can be seen that these preparation processes all require heat treatment processes such as drying and calcining to remove a large amount of solvent in the gel system to obtain the final composite material. However, the solvent removal process (especially the aqueous solvent system) will inevitably lead to the condensation and collapse of the gel system structure, which will not only cause SiO 2 The decrease in specific surface area and the blockage of pores will also cause the nano-metal particles to aggregate and grow to varying degrees. For this reason, patent CN 201811356599 discloses a ZnO-SiO 2 Composite aerogel and preparation method thereof, first preparing ZnO solution, then adding it dropwise to SiO 2 In the aerogel precursor, the mixture is subjected to the processes of standing gelation, aging, solvent replacement, surface modification, drying and hydrophilic treatment (high temperature calcination) to obtain ZnO-SiO 2 Composite aerogel. In order to inhibit the condensation and collapse of the material structure caused by the removal of solvents such as water during the drying process, after the gel is aged, the water and other solvents are replaced with n-hexane; the gel surface is modified with trimethylchlorosilane and the like to increase the hydrophobicity of the gel surface to remove the adsorbed water; finally, high-temperature calcination is performed to remove trimethylchlorosilane and the like, and the surface hydroxyl groups of the aerogel are restored to make the material hydrophilic. The preparation of this material involves multiple steps, a complex process, and the use of toxic organic reagents. Patent CN202111178826 discloses a bimetallic element doped SiO 2Composite nanomaterials and preparation methods thereof, firstly, metal salts, organic ligands and solvents are mixed, and metal coordination polymers are obtained through complexation reaction and drying, and then the metal coordination polymers are mixed with tetraethyl orthosilicate, ammonia water, etc., and solvent thermal reaction, drying and roasting are performed to obtain composite nanomaterials. In order to inhibit the aggregation of nanometal particles during drying and roasting, organic ligands are used in advance to reduce the migration freedom of metals and confine the metals in a limited space. This process requires the use of a large amount of expensive organic ligands, which reduces the economic efficiency of the process. Patent CN 201680045373 discloses a preparation of a metal oxide-silicon dioxide composite aerogel: in the first step, a metal ion solution is added to a water glass solution, and a metal oxide-silicon dioxide composite agglomerate is prepared by reaction under acidic conditions; in the second step, an alkali catalyst is added thereto to react to prepare a metal oxide-silicon dioxide composite wet gel, and finally the final material is obtained by drying. This process adopts a two-step method. In the first step, the metal ions are anchored on SiO 2 In the second step, the metal ions are precipitated to form metal oxides with relatively large size and relatively weak mobility, which further limits their mobility in SiO 2 This process requires the use of acid (such as hydrochloric acid, sulfuric acid, hydrofluoric acid, etc.) and alkali (sodium hydroxide, potassium hydroxide, etc.) catalysts, which is not conducive to environmental protection.

[0005] In summary, the current metal oxide-SiO 2 In the preparation of composite materials, there is a problem of metal oxide aggregation and growth during the process of drying, calcination and solvent removal. In order to inhibit the aggregation of metals, it is highly dispersed in SiO 2 In the three-dimensional structure, the existing preparation methods have problems such as complex process, uneconomical process or environmentally unfriendly process. Summary of the invention

[0006] For the current metal oxide-SiO 2 In the preparation method of the composite material, the metal oxide has the problem of aggregation and growth during the process of removing the solvent such as drying and calcining. The present invention provides a high specific surface area SiO 2 -Metal oxide composite materials and their preparation methods and applications.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] In the first aspect, the present invention provides a high specific surface area SiO 2 -Method for preparing metal oxide composite materials, in which a polyhydroxy polymer compound is added during the mixing process of silicon source, metal salt and solvent to inhibit the SiO 2 The collapse of the structure and the aggregation and growth of metal oxides produced SiO2 -Metal oxide composites, in which metal oxides are highly dispersed in SiO in the form of small-sized nanoparticles 2 The specific steps are as follows:

[0009] Step 1: fully and uniformly mix the silicon source, metal salt, solvent and polyhydroxy polymer compound to obtain a mixture;

[0010] Step 2: Dry and calcine the mixture to obtain SiO 2 -Metal oxide composite materials.

[0011] In this technical solution, the hydroxyl groups in the polyhydroxy polymer compound can be used as adsorption sites to compete with the hydroxyl groups in the solvent molecules (especially water) to adsorb the silicon source precursor and metal ions. On the one hand, this "squeezes out" the solvent molecules adsorbed around the silicon source and metal ions, and on the other hand, it confines the metal ions to the polyhydroxy polymer compound, thereby reducing its range of movement and weakening its freedom of movement. By adding more polyhydroxy polymer compounds, the number of solvent molecules around the silicon source and metal ions is as small as possible, and the number of polyhydroxy polymer compounds is as large as possible. In the process of removing the solvent such as drying and roasting, SiO 2 There are fewer solvent molecules around the precursor, and SiO 2 The structure is not easy to collapse, and its specific surface area is high, which can inhibit the metal from 2 At the same time, there are few solvent molecules around the metal ions, and they are confined in the polyhydroxy polymer compound, which is conducive to obtaining small-sized nano-metal oxide particles and also to their high dispersion in SiO 2 In the structure.

[0012] Furthermore, in step 1, the silicon source is any one or a combination of sodium silicate, tetraethyl orthosilicate, tetramethyl orthosilicate, and silica sol. The above silicon source can easily form a rich three-dimensional pore structure and a large specific surface area through hydrolysis, condensation reaction, etc. in the solvent system, which is conducive to the dispersion of metal oxides therein.

[0013] Furthermore, in step 1, the metal salt is any one or a combination of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate, aluminum nitrate, ruthenium trichloride hydrate, and tetraammine platinum chloride hydrate. Metal nitrates have high solubility in solvents such as water, a wide adjustable concentration range, and solutions of metal nitrates are usually weakly acidic, which is conducive to the pre-hydrolysis and preliminary polycondensation reaction of silicon source molecules. Precious metal salt hydrates can be dissolved in low-carbon alcohols (such as methanol, ethanol, propanol, isopropanol, etc.) and low-carbon alcohol-water solutions, and the free metal ions produced are easy to interact with the hydroxyl groups of the polyhydroxy polymer compound, and then adsorbed on the polyhydroxy polymer compound.

[0014] Furthermore, the solvent in step 1 is any one or a combination of water, methanol, ethanol, propanol, and isopropanol. These solvents can dissolve and disperse the silicon source, metal salt, and polyhydroxy polymer compound well, so that they can reach a uniform mixing state, so that the hydroxyl group of the polyhydroxy polymer compound can fully contact and adsorb the silicon source and the metal ions.

[0015] Furthermore, the polyhydroxy polymer compound in step 1 is any one or a combination of polyvinyl alcohol, soluble starch, corn starch, potato starch, and potato starch. These polyhydroxy polymer compounds contain abundant hydroxyl groups and have strong ability to adsorb silicon sources and metal ions. When they compete with solvent molecules to adsorb silicon sources and metal ions, they can "squeeze out" solvent molecules and adsorb them, and accumulate around silicon sources and metal ions.

[0016] Furthermore, the masses of the silicon source and the metal salt in step 1 are respectively SiO 2 Calculated based on the total mass of the silicon source and the metal salt, the mass of the polyhydroxy polymer compound is 10-30 times the total mass of the silicon source and the metal salt.

[0017] The main function of the polyhydroxy polymer compound is to compete with the solvent molecules to adsorb the silicon source and copper ions, thereby stabilizing the silicon source and copper ions. Experiments have shown that when the amount of the polyhydroxy polymer compound added is 10-30 times the total mass of the silicon source and the metal salt, the polyhydroxy polymer compound has a good adsorption effect on the silicon source and copper ions. When the amount of the polyhydroxy polymer compound added is too much, it cannot further promote the adsorption of the silicon source and copper ions, but will only increase the raw material consumption and increase the process cost. When the amount of the polyhydroxy polymer compound added is too little, the polyhydroxy polymer compound is difficult to compete with the solvent molecules to adsorb the silicon source and copper ions, which is not conducive to the adsorption stability of the silicon source and metal ions.

[0018] Furthermore, in step 1, the silicon source, metal salt, and solvent are calculated according to the molar number of silicon atoms, the total molar number of metal ions, and the volume of the solvent, respectively, and the ratio of the silicon source, metal salt, and solvent is in the range of 1 mol: 0.005-3 mol: 100-5000 mL. If the molar ratio of metal to silicon is too low, the particles of metal oxide are too small and are easily embedded in SiO 2 The inner wall of the pores is not easy to interact with the adsorbate molecules or reactant molecules. The molar ratio of metal to silicon is too high, and the large amount of metal oxide particles formed is not conducive to the SiO 2 The formation of a three-dimensional structure. If the volume of the solvent is too small, the silicon source, metal salt and polyhydroxy polymer compound cannot be fully dissolved and dispersed, and it is difficult to achieve a uniform mixing state; if the volume of the solvent is too large, there are too many solvent molecules adsorbed around the silicon source and metal ions, which hinders the competitive adsorption of the polyhydroxy polymer compound around the silicon source and metal ions.

[0019] Furthermore, the drying conditions in step 2 are: temperature of 60-150°C and time of 0.5-20.0h. Low drying temperature is not conducive to the removal of solvent molecules from the system; high drying temperature makes the polyhydroxy polymer compound unstable, and its ability to confine metal ions decreases, resulting in enhanced mobility of metal ions, which is not conducive to high dispersion of metal ions in the system. Short drying time leads to incomplete solvent removal and long drying time, which increases energy consumption and cost of the process.

[0020] Furthermore, the calcination conditions in step 2 are: temperature of 200-600°C, air atmosphere, and time of 2-12 hours. When calcination is carried out under this temperature, atmosphere, and time range, it is conducive to the formation of metal oxides highly dispersed in SiO 2 The structure is also conducive to removing polyhydroxy polymer compounds, enriching the pore structure of the composite material, and increasing its specific surface area. When the reaction time is too short and the temperature is too low, it is difficult to completely remove the residual solvent in the system; when the reaction time is too long and the temperature is too high, SiO 2 The structure is prone to collapse, and metal oxides are prone to aggregation and growth.

[0021] In a second aspect, the present invention provides a high specific surface area SiO 2 - A metal oxide composite material, prepared by the preparation method described in the first aspect.

[0022] In a third aspect, the present invention provides the high specific surface area SiO 2 - Application of metal oxide composites for catalysis of reverse water gas shift reaction and / or adsorption of CO 2 .

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention utilizes the ability of hydroxyl groups in polyhydroxy polymer compounds to adsorb silicon sources and metal ions, forming competitive adsorption with solvent molecules to replace the solvent molecules around the silicon sources and metal ions; in addition, the hydroxyl groups and network structure of the polyhydroxy polymer compounds are used to confine metal ions, thereby reducing their freedom of migration in the system; the combined effect of the above two aspects inhibits the SiO2 from being absorbed during the solvent removal process such as drying and calcination. 2 The condensation collapse of the structure and the aggregation growth of the metal oxide precursors.

[0025] (2) The preparation process of the present invention is simple, easy to control, and environmentally friendly, and does not use inorganic acids and alkalis that are harmful to the environment and human body, or toxic organic raw materials.

[0026] (3) The present invention does not use an expensive solvent system, has good economic efficiency, and has good industrial application prospects.

[0027] (4) SiO of the present invention 2 -Metal oxide composites have a high specific surface area, and the metal oxides are highly dispersed in the SiO 2 In the structure, it is used to adsorb CO 2 When the material is CO 2 It has a large adsorption capacity and is highly active and selective when used to catalyze the reverse water-gas shift reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SiO 2 N-metal oxide composites 2 - Physical adsorption-desorption curve diagram (wherein, Figure 1 a-1g are the composite materials of Examples 1-7 respectively).

[0029] Figure 2 SiO 2 - X-ray diffraction pattern of the metal oxide composite material (wherein, Figure 2 a-2g are the composite materials of Examples 1-7 respectively).

[0030] Figure 3 SiO 2 -High magnification transmission electron microscopy image of metal oxide composite material (wherein, Figure 3 a-3b is the composite material of Example 1, Figure 3 c-3d is the composite material of Example 2). DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] Example 1

[0033] 0.1 mol of tetraethyl orthosilicate (SiO 2 The mass of the mixture is 6.01 g), 0.18 mol of zinc nitrate (hexahydrate) (the mass of ZnO is 14.65 g), 0.12 mol of copper nitrate (trihydrate) (the mass of CuO is 9.55 g), 160 mL of deionized water, 240 mL of ethanol, and 604 g of potato starch (the mass of SiO 2 , ZnO and CuO) were mixed in a 2000 mL beaker by mechanical stirring, and the obtained uniform mixture was dried at 120 ° C for 6 h, and calcined at 600 ° C in air atmosphere for 2 h to obtain the final SiO 2-Metal oxide composites, labeled as SiO 2 -Zn-Cu.

[0034] SiO 2 -Zn-CuN 2 -Physisorption-desorption curves are shown in Figure 1 a, the texture properties are shown in Appendix 1, and its specific surface area is 633.2m 2 / g, with an average pore size of 2.4nm, which is a typical mesoporous material. 2 -X-ray diffraction (XRD) pattern of Zn-Cu is shown in Figure 2 a, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks of CuO and ZnO were not observed, indicating that CuO and ZnO were dispersed in the system as nanoparticles, and the particle sizes of both were below the XRD detection limit (XRD detection limit: solid particle size ≤ 5nm). 2 -High magnification transmission electron microscopy (HRTEM) image of Zn-Cu is shown in Figure 3 a-3b, SiO 2 It has an amorphous structure with worm-like mesoporous channels. The average particle sizes of CuO and ZnO nanoparticles are 3.4nm and 3.0nm, respectively.

[0035] The SiO 2 -Zn-Cu catalytic performance in the reverse water-gas shift reaction. 2 / CO 2 =5:1 (volume ratio), pressure 3.0MPa and air velocity 2.0NL / g-cat / h, after 24h of reaction, SiO 2 -Zn-Cu reaches a steady state. Its CO 2 The conversion rate was 55.3%, and the selectivity of the product carbon monoxide (CO) was 99.1 mol%.

[0036] Example 2

[0037] 0.1 mol of tetraethyl orthosilicate (SiO 2 The mass of the mixture was 6.01 g), 0.1 mol of zinc nitrate (hexahydrate) (the mass of ZnO was 8.14 g), 100 mL of deionized water, 200 mL of propanol, and 424.20 g of potato starch (the mass of SiO 2 The mixture was dried at 110 °C for 12 h and calcined at 450 °C in air for 10 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO2 -Zn.

[0038] SiO 2 -ZnN 2 -Physisorption-desorption curves are shown in Figure 1 b. The texture properties are shown in Appendix 1. Its specific surface area is 549.4 m 2 / g, with an average pore size of 4.0nm, which is a typical mesoporous material. 2 -Zn X-ray diffraction (XRD) pattern is shown in Figure 2 b, SiO 2 It is a typical amorphous structure; except for SiO 2 No diffraction peak of ZnO was observed, indicating that the particle size of ZnO is below the detection limit of XRD. 2 -Zn high magnification transmission electron microscopy (HRTEM) image is shown in Figure 3 c-3d, SiO 2 It has an amorphous structure with worm-like mesoporous channels, and the average particle size of ZnO nanoparticles is 4.0 nm.

[0039] Using CO 2 Static adsorption characterization investigated the SiO 2 -Zn adsorption of CO 2 At room temperature and pressure, SiO 2 -Zn adsorption of CO 2 The amount is 5.58 mmol / g.

[0040] Example 3

[0041] 0.1 mol of tetramethyl orthosilicate (SiO 2 The mass of the mixture is 6.01 g), 0.05 mol of zinc nitrate (hexahydrate) (the mass of ZnO is 4.07 g), 0.05 mol of copper nitrate (trihydrate) (the mass of CuO is 3.98 g), 0.05 mol of aluminum nitrate (nonahydrate) (Al 2 O 3 The mass of the mixture is 2.55 g), 100 mL of deionized water, 200 mL of methanol, and 415.00 g of soluble starch (the mass of which is SiO 2 , ZnO, CuO and Al 2 O 3 The mixture was dried at 60 °C for 20 h and calcined at 200 °C in air for 12 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO 2 -Zn-Cu-Al.

[0042] SiO2 -Zn-Cu-Al N 2 -Physisorption-desorption curves are shown in Figure 1 c, the texture properties are shown in Appendix 1, and its specific surface area is 453.8m 2 / g, with an average pore size of 2.8nm, which is a typical mesoporous material. 2 -X-ray diffraction (XRD) pattern of Zn-Cu-Al is shown in Figure 2 c, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks, no CuO, ZnO and Al were observed 2 O 3 The diffraction peaks of CuO, ZnO and Al 2 O 3 The three materials are dispersed in the system in the form of nano-sized particles, and their particle sizes are all below the detection limit of XRD.

[0043] Using CO 2 Static adsorption characterization investigated the SiO 2 -Zn-Cu adsorption of CO 2 At room temperature and pressure, SiO 2 -Zn-Cu adsorption of CO 2 The amount is 3.35 mmol / g.

[0044] Example 4

[0045] 0.1 mol of sodium silicate (SiO 2 The mass is 6.01 g), 0.045 mol of iron nitrate (nonahydrate) (Fe 2 O 3 The mass of the mixture is 3.60 g), 0.005 mol of manganese nitrate (trihydrate) (the mass of MnO is 0.35 g), 80 mL of deionized water, 20 mL of propanol, and 149.25 g of corn starch (the mass of SiO 2 , Fe 2 O 3 The mixture was ground in a ball mill until uniformly mixed, and the uniform mixture was dried at 150 °C for 0.5 h and calcined at 580 °C in air atmosphere for 2 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO 2 -Fe-Mn.

[0046] SiO 2 -Fe-Mn N 2 -Physisorption-desorption curves are shown in Figure 1 d, the texture properties are shown in Appendix 1, and its specific surface area is 369.7m 2 / g, with an average pore size of 2.9nm, which is a typical mesoporous material. 2 The X-ray diffraction (XRD) pattern of Fe-Mn is shown in Figure 2 d, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks, no Fe was observed 2 O 3 and MnO diffraction peaks, indicating that Fe 2 O 3 and MnO are dispersed in the system in the form of nanoparticles, and the particle sizes of both are below the detection limit of XRD.

[0047] Example 5

[0048] 24.04 g of silica sol (acidic, containing 0.1 mol SiO 2 , corresponding to SiO 2 The mass is 6.01 g), 0.0005 mol of tetraammine platinum chloride hydrate (PtO 2 The mass of the mixture is 0.11 g), 2 mL of deionized water, 8 mL of isopropanol, and 61.11 g of potato starch (the mass of which is SiO 2 and PtO 2 The mixture was dried at 100 °C for 10 h and calcined at 500 °C in air for 6 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO 2 -Pt.

[0049] SiO 2 -PtN 2 -Physisorption-desorption curves are shown in Figure 1 e, the texture properties are shown in Appendix 1, and its specific surface area is 227.6m 2 / g, with an average pore size of 4.3nm, which is a typical mesoporous material. 2 -Pt X-ray diffraction (XRD) pattern is shown in Figure 2 e, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks, no PtO observed 2 The diffraction peaks of PtO 2 The nanoparticles are dispersed in the system, and the particle size is below the lower limit of XRD detection.

[0050] Example 6

[0051] 0.1 mol of sodium silicate (SiO 2The mass of the raw materials is 6.01 g), 0.198 mol of zinc nitrate (hexahydrate) (the mass of ZnO is 16.12 g), 0.002 mol of ruthenium chloride hydrate (RuO 2 The mass of SiO is 0.27 g), 500 mL of deionized water and 223.90 g of polyvinyl alcohol (the mass of SiO 2 , ZnO and RuO 2 The mixture was dried at 80 °C for 14 h and calcined at 350 °C in air for 12 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO 2 -Zn-Ru.

[0052] SiO 2 -Zn-RuN 2 -Physisorption-desorption curves are shown in Figure 1 f, the texture properties are shown in Appendix 1, and its specific surface area is 506.2m 2 / g, with an average pore size of 2.5nm, which is a typical mesoporous material. 2 -X-ray diffraction (XRD) pattern of Zn-Ru is shown in Figure 2 f, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks, no ZnO and RuO were observed 2 The diffraction peaks of ZnO and RuO 2 The nanoparticles are dispersed in the system, and the particle size is below the lower limit of XRD detection.

[0053] Example 7

[0054] 0.1 mol of a mixture of methyl orthosilicate and ethyl orthosilicate (wherein the molar ratio of methyl orthosilicate to ethyl orthosilicate is 1:1, containing SiO 2 The total mass is 6.01 g), 0.0004 mol of tetraammine platinum chloride hydrate (PtO 2 The mass is 0.091 g), 0.0005 mol of ruthenium trichloride hydrate (RuO 2 The mass of SiO is 0.067 g), 50 mL of ethanol, 30.70 g of polyvinyl alcohol (the mass of SiO 2 , PtO 2 and RuO 2 5 times the total mass) and 92.37 g of potato starch (whose mass is SiO 2 , PtO 2 and RuO 2The mixture was dried at 120 °C for 12 h and calcined at 550 °C in air for 4 h to obtain the final SiO 2 -Metal oxide composites, labeled as SiO 2 -Pt-Ru.

[0055] SiO 2 -Pt-Ru N 2 -Physisorption-desorption curves are shown in Figure 1 g, the texture properties are shown in Appendix 1, and its specific surface area is 358.6m 2 / g, with an average pore size of 2.9nm, which is a typical mesoporous material. 2 -X-ray diffraction (XRD) pattern of Pt-Ru is shown in Figure 2 g, SiO 2 It is a typical amorphous structure; except for SiO 2 Diffraction peaks, no ZnO and RuO were observed 2 The diffraction peaks of ZnO and RuO 2 The nanoparticles are dispersed in the system, and the particle size is below the lower limit of XRD detection.

[0056] Table 1 SiO in each embodiment 2 -Preparation conditions and characterization results of metal oxide composites

[0057]

[0058] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing a high specific surface area SiO2-metal oxide composite material, characterized in that: The steps include: Step 1: fully and uniformly mix the silicon source, metal salt, solvent and polyhydroxy polymer compound to obtain a mixture; Step 2: Drying and calcining the mixture to obtain a SiO2-metal oxide composite material.

2. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: In step 1, the silicon source is any one of sodium silicate, tetraethyl orthosilicate, tetramethyl orthosilicate, and silica sol, or a combination of several of them.

3. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: The metal salt in step 1 is any one or a combination of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate, aluminum nitrate, ruthenium trichloride hydrate, and tetraammine platinum chloride hydrate.

4. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: The solvent in step 1 is any one of water, methanol, ethanol, propanol, and isopropanol, or a combination thereof.

5. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: In step 1, the polyhydroxy polymer compound is any one of polyvinyl alcohol, soluble starch, corn starch, potato starch, and potato starch, or a combination of several of them.

6. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: In the step 1, the masses of the silicon source and the metal salt are calculated as SiO2 and metal oxide, respectively, and the mass of the polyhydroxy polymer compound is 10-30 times the total mass of the silicon source and the metal salt.

7. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: In the step 1, the silicon source, metal salt and solvent are calculated according to the molar number of silicon atoms, the total molar number of metal ions and the volume of the solvent, respectively. The ratio of the silicon source, the metal salt and the solvent is in the range of 1 mol: 0.005-3 mol: 100-5000 mL.

8. The method for preparing a high specific surface area SiO2-metal oxide composite material according to claim 1, characterized in that: The drying conditions in step 2 are: temperature of 60-150° C., time of 0.5-20.0 h; the calcination conditions are: temperature of 200-600° C., air atmosphere, time of 2-12 h.

9. A high specific surface area SiO2-metal oxide composite material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the high specific surface area SiO2-metal oxide composite material according to claim 9, characterized in that: Used to catalyze the reverse water gas shift reaction and / or adsorb CO2.

Citation Information

Patent Citations

  • Method for manufacturing metal oxide-silica composite aerogel and metal oxide-silica composite aerogel manufactured thereby

    CN107922201A

  • ZnO / SiO2 composite aerogel material and preparation method thereof

    CN109894074A

  • A bimetallic element doped silicon dioxide composite nanomaterial and its preparation method and application

    CN115957762B